Identifying kinesiophobia subtypes and their determinants in patients with hip fractures: a latent profile analysis - Cao, Yue; Lan, Xuefen; Li, Caifu; Xiang, Yingmei; Xu, Qiyao; Zhang, Ruilin; Li, Min (Frontiers in Psychiatry, 2026)
BackgroundLimited attention to middle-aged and younger populations has obscured important age-related differences in fear-avoidance mechanisms. Moreover, most existing research on kinesiophobia focuses narrowly on single disease groups and lacks a systematic examination of the multi-dimensional “pain cognition-fear emotion-avoidance behavior” framework. These gaps have led to uniform interventions that overlook diverse fear triggers, hindering precision case and wasting medical resources.ObjectiveTo identify latent subtypes of kinesiophobia in patients with hip fractures, examine their clinical characteristics, and explore associated factors and intergroup differences, with the aim of informing more targeted intervention strategies.MethodsThis cross-sectional study was conducted between November 2024 and June 2025. Patients with clinically diagnosed hip fractures were recruited through convenience sampling from the orthopedic wards of two tertiary hospitals and two community healthcare centers in Lishui City. Data were collected using the General Information Questionnaire, Tampa Scale for Kinesiophobia (TSK), Self-Rating Scale of Sleep (SRSS), Tilburg Frailty Indicator (TFI), and Visual Analogue Scale (VAS), and subsequently analyzed with SPSS version 27.0. Univariate and multivariate logistic regression analyses were conducted to identify significant predictors of subgroup membership, with the low avoidance type as the reference. Latent profile analysis was conducted using Mplus version 8.3. Among the tested models, the three-class solution (Model 3; AIC = 12738.385, BIC = 13006.411, aBIC = 12784.358, entropy = 0.963) demonstrated the best fit and was selected as the optimal model.ResultsA total of 340 patients with hip fractures were included, with a mean TSK score of 46.68 ± 12.33. Latent profile analysis revealed three distinct kinesiophobia subtypes: low avoidance type, 29.7%, cautious avoidance type, 17.6%, and prominent avoidance type, 52.6%. Logistic regression analysis indicated that academic level, comorbid painful conditions, pain intensity (5.59 ± 3.16), frailty (8.91 ± 4.81), and sleep disturbances (30.99 ± 11.47) were independent predictors of subgroup membership (P < 0.05).ConclusionThis study identified three kinesiophobia subtypes among patients with hip fractures, supporting the relevance of the fear-avoidance model in trauma rehabilitation and providing a basis for tailored intervention strategies (e.g., multimodal therapies for the subtype of significant avoidance kinesiophobia) to optimize rehabilitation outcomes. Future research should investigate the longitudinal trajectory of these subtypes, evaluate the sustained effects of targeted interventions, and examine the generalizability of the model to guide precision rehabilitation care.